Survival in patients diagnosed with castration-resistant prostate cancer: a population-based observational study in Sweden. (3rd March 2020) - Aly, Markus; Leval, Amy; Schain, Frida; Liwing, Johan; Lawson, Joe; Vágó, Emese; Nordström, Tobias; Andersson, Therese M.-L.; Sjöland, Erik; Wang, Chen; Eloranta, Sandra; Akre, Olof
Abstract: Background: This study investigated prostate cancer (PC)-specific survival and overall survival (OS) in a population-based castration-resistant PC (CRPC) cohort. Methods: Data from Stockholm Prostate-Specific Antigen (PSA) and Biopsy Register patients with increasing PSA despite gonadotropin-releasing hormone treatment or surgical castration ( n = 1, 712) included PSA values and biopsies from 2003 to 2015 and were linked to the National Prostate Cancer Register and Prescribed Drug Register. Kaplan-Meier method estimated PC-specific survival and OS, stratified by metastasis at PC diagnosis, and Cox regression estimated hazard ratios (HRs) for Gleason score and T-stage at PC diagnosis and for age and calendar period at CRPC onset by metastasis status at diagnosis. Results: Median OS after CRPC onset was 23.2 months (95% CI = 21.0–25.9) among patients without metastases (M0) at primary diagnosis, and 13.2 months (11.3–14.5) among patients with metastases (M1). Median PC-specific survival from CRPC onset was 30.3 (27.5–34.1) months and 13.3 (12.1–15.8) months for M0 and M1 patients, respectively. Biopsy Gleason score ≥ 8 was associated with higher all-cause mortality than ≤6 (HR = 2.07 [95% CI = 1.43–3.01]) and PC-specific mortality (2.07 [1.27–3.40]) after CRPC among patients with M0 disease. Patients developing CRPC from 2012 onward had lower all-cause mortality (HR = 0.71 [95% CI = 0.60–0.85] [M0]; 0.60 [0.47–0.77] [M1]) and PC-specific mortality (0.73 [0.57–0.94] [M0]; 0.62 [0.46–0.84] [M1]) compared with those prior to 2012. Conclusions: M1 disease at PC diagnosis was associated with worse survival after CRPC onset versus M0. Higher Gleason score at diagnosis was associated with higher mortality after CRPC onset in M0 patients at diagnosis.